A reinstatement and a new combination in Morella subgenus Morella (Myricaceae), with typification of Myrica integrifolia - Vashi, Chipem; Shankar, Uma; Misra, Arvind K. (Phytotaxa, 2017)
Myrica integrifolia is the first Myrica sensu lato species described from India by Roxburgh in 1832. The specific identity of M. integrifolia has been lost due to vague morphological species boundary between M. integrifolia and a closely related species, M. esculenta (≡ Morella esculenta). A detailed morphological analysis carried out on the living specimens of these two species which co-occur in Meghalaya, India and their type materials revealed that M. intergrifolia is a distinct taxon. M. integrifolia is distinguished from M. esculenta by indumenta of twigs, petioles and leaves, colour and micromorphology of peltate trichomes, staminate and pistillate inflorescences, infructescences and fruit characters. We, therefore, reinstate the specific status of M. integrifolia and reassign it in the genus Morella. A new combination of name, Morella integrifolia is thus proposed for M. integrifolia which is also designated with a lectotype and an epitype for the basionym.